2-hydroxyglutarate mediates whitening of brown adipocytes coupled to nuclear softening upon mitochondrial dysfunction - Kaul, Harshita; Isermann, Lea; Senft, Katharina; Popovic, Milica; Georgomanolis, Theodoros; Baumann, Linda; Sivanesan, Pujyanathan; Pouikli, Andromachi; Nolte, Hendrik; Lucic, Bojana; Hildebrandt, Ximena; Seidel, Katrin; et al. (Nature metabolism, 2025)
Mitochondria have a crucial role in regulating cellular homeostasis in response to intrinsic and extrinsic cues by changing cellular metabolism to meet these challenges. However, the molecular underpinnings of this regulation and the complete spectrum of these physiological outcomes remain largely unexplored. In this study, we elucidate the mechanisms driving the whitening phenotype in brown adipose tissue (BAT) deficient in the mitochondrial matrix protease CLPP. Here we show that CLPP-deficient BAT shows aberrant accumulation of lipid droplets, which occurs independently of defects in oxygen consumption and fatty acid oxidation. Our results indicate that mitochondrial dysfunction due to CLPP deficiency leads to the build-up of the oncometabolite d-2-hydroxyglutarate (d-2HG), which in turn promotes lipid droplet enlargement. We further demonstrate that d-2HG influences gene expression and decreases nuclear stiffness by modifying epigenetic signatures. We propose that lipid accumulation and altered nuclear stiffness regulated through 2HG are stress responses to mitochondrial dysfunction in BAT.